Lower-limb neurologic deficit after vaginal delivery: a prospective observational study. (February 2020) - Tournier, A.; Doremieux, A.C.; Drumez, E.; Labreuche, J.; Cassim, F.; Bartolo, S.; Richart, P.; Garabedian, C.; Subtil, D.
Highlights: Lower limb neurologic deficit affected 0.3% of vaginal deliveries. Most deficits were sensory (67.7%) and concerned femoral nerve territory (83.9%). The median time to recovery was 18 days. Most women (69.2%) recovered within six weeks. 11% continued to have a deficit one year later. Abstract: Background: Lower limb neurologic deficit after vaginal delivery remains poorly understood. The objective of this study was to describe the incidence, characteristics and prognosis associated with nerve injury occurring to women during vaginal delivery. Methods: A single-center observational study of women who complained about a lower limb neurologic deficit that appeared immediately after vaginal delivery. The follow-up period was up to four years. Results: Among the 10 569 women with a singleton vaginal delivery during the 30-month study period, 31 (0.3%) reported a neurologic deficit. Most women were nulliparous (71%) and the mean duration of the second stage of labor was 94 min [range 13–224 min]. In two-thirds of cases, delivery required instrumental assistance. Most neurologic deficits were sensory (67.7%) and primarily involved femoral nerve territory (83.9%). Most women recovered within six weeks (69.2%). In one case (a sensory deficit of the entire right leg), recovery only occurred after 3.5 years. Conclusion: Neurologic deficit was identified in 0.3% of our vaginal delivery population. Recovery from neurologic deficit may take many weeks and may occasionally be disabling.